Large Language Models and Medical AI Systems for Healthcare Diagnosis: A Systematic Review - M. U. K. Gunawardhna; Pirunthavi Wijikumar; D. M. O. K. Weerasinghe (Sri Lankan Journal of Applied Sciences, 2026)
The rapid growth of artificial intelligence systems (AI systems) has increased interest in the use of patient care and clinical decision-making processes. There is some uncertainty regarding their reliability and safety in clinical practice. A more detailed systematic review of literature examining LLMs applied to healthcare diagnosis was conducted. A PRISMA-based systematic review has been carried out of relevant literature published in the major databases for the years 2022–2025. Key findings include a growing trend to develop multimodal models based on diverse input modalities, combining LLM models with other models as part of clinical workflows. The Usage of complementary methodologies such as retrieval-augmented generation, knowledge graphs, and federated learning is highly expanding, particularly in enhancing the efficiency and accuracy of clinical decision-making processes. Significant challenges such as hallucinations, bias, prompt sensitivity, limited explainability, and inadequate clinical validation continue to pose major obstacles. Although promising, LLM-based systems are not yet reliable enough for autonomous medical diagnosis. Overall, this review contains multiple recommendations for future research in many areas (e.g., LLMs) to ensure a high level of safety, transparency, and clinical applicability for LLMs and other AI/ML-related technologies and devices.